Implementation of murabahah agreement at KPPS – BMT Al-Hikmah Semesta Jatim Karagploso Branch - Nuriyah, Neng Liana Shinta (Maliki Interdisciplinary Journal, 2024)
Within the scope of sharia economics, there are various principles and contracts that are often used in economic activities that comply with sharia economics, for example in the practice of murabahah financing products. Even though the Murabahah contract is generally implemented, most people still do not understand how it is implemented. The author discusses how the implementation of Murabahah financing products at a sharia financial institution such as BMT Alhikmah Karangploso branch. This research article applies qualitative methods with a descriptive approach, which aims to explain and describe existing phenomena or situations, whether they come from nature or are the result of human engineering. Based on the results of research conducted using a descriptive approach, it was found that the implementation of murabahah financing to partners at KSPPS BMT Al-Hikmah was carried out using a murabahah bil wakalah contract, where the Ijab Qabul was carried out after it officially became the property of BMT. This practice is in accordance with the fatwa of the MUI National Sharia Council as regulated in the Murabahah document 04/DSN MUI/IV/2000, which requires KSPPS to legally purchase assets required by customers and offer them to customers.